Los siete pecados capitales de la capital y el desarrollo de la región del Bío-Bío. Un binomio para potenciar la calidad de vida - Boisier, Sergio (Revista EURE - Revista de Estudios Urbano Regionales, 1989)
The author points out what he defines as the more serious problems affecting inhabitants of Santiago, the same as for other third world mega-polis. Among them, the deterioration of environmental conditions -specially the atmospheric contamination- is clearly perceived by people as a social sin. The only way out in the medium and long term seems to be to regulate the increasing size of the capital city both in physical and in economic terms. Í